Pendekatan Sosiologis dan Antropologis dalam Penyebaran Agama Oleh Wali Songo - Mardena, Yully; Bukhari, Bukhari (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2019)
Walisongo means guardian of Nine, namely Nine people who love and are loved by Allah, preach spreading Islam in areas that have not embraced Islam on Java. Era Walisongo is the era of the end of Hindu-Buddhist domination in the culture of the archipelago to be replaced with Islamic culture. They are a symbol of the spread of Islam in Indonesia. Especially in Java. Of course many other characters also play a role. The sociology of da'wah is the study of the relationships between the process of da'wah and social processes, while the anthropology of da'wah concentrates the process of da'wah in its cultural aspects. There are a number of Walisongo propaganda movements that use sociological and anthropological approaches including: First, through the Sufistic approach. Walisongo made a sufistic approach to preaching, including Sunan Bonang and Sunan Kalijaga. The process of assimilating Hindu Buddhist religious traditions such as Sradha (meruwat ceremony of spirits after twelve years of death). A new tradition of Islam was born called Nyradha or Nyadran (the ceremony of sending prayers to spirits). Second, Da'wah through assimilation of education. Da'wah through assimilation of education through Islamic boarding schools, magicians and colleges through langgar, tajuk, mosques and children's games. Walisongo formulated the values of monotheism and Shiva-Buddha (adwayasashtra) with the teachings of Islamic monotheism adopted by Sufi teachers. Third, Da'wah through art and culture. Cultural art was used as an effective means of da'wah by Walisongo in the dissemination of various values, understandings, concepts, ideas, views and ideas originating from Islamic teachings. Assimilation through cultural arts is done like changing the puppet about the gods with the genealogy of the prophet Adam. Da'wah Walisongo is flexible by incorporating Islamic teachings into existing traditions so as not to erase traditions that have become a habit of the people at that time. After entering Islam, new Islamic law is taught. The next task of the preacher is to improve da'wah in the community.